Correction: The synthesis of calcium arsenate@iron arsenate coating materials and their application for arsenic-containing wastewater treatment. Issue 7 (22nd January 2020) - Wang, Yang; Rong, Zhihao; Tang, Xincun; Cao, Shan
Abstract : Correction for 'The synthesis of calcium arsenate@iron arsenate coating materials and their application for arsenic-containing wastewater treatment' by Yang Wang et al., RSC Adv., 2020, 10, 719–723.